Experimental Study of Spark Ignition Engine Performance under Different Electronic Control Units, Hole Injectors and Spark Plugs - Aureo Adriyanto Da Costa Amaral; Naili Saidatin; Hasan Syafik Maulana (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2023)
The passage discusses the use of technology in vehicle fuel systems, specifically the injection system technology that is replacing conventional fuel systems. One crucial component of the fuel injection system is the Engine Control Unit (ECU), which controls the distribution of current to all engine components. While standard ECUs used on motorcycles today have limitations, racing ECUs provide more quality and can improve engine performance. The study aims to evaluate the engine's performance after modifications with an upgraded racing ECU using an 8-hole injector and racing spark plugs in the ignition system to enhance the motorcycle's performance. The methods and analysis section details the tools utilized, including the chassis dynamometer, and the parameters used in the study. The results and discussions section presents the collected data and compares it with previous studies to validate the observations.